A cross‐standardized flow cytometry platform to assess phenotypic stability in precursor B‐cell acute lymphoblastic leukemia (B‐ALL) xenografts. Issue 1 (25th June 2021) - Rolf, Nina; Liu, Lorraine Y. T.; Tsang, Angela; Lange, Philipp F.; Lim, Chinten James; Maxwell, Christopher A.; Vercauteren, Suzanne M.; Reid, Gregor S. D.
Abstract: With the continued poor outcome of relapsed acute lymphoblastic leukemia (ALL), new patient‐specific approaches for disease progression monitoring and therapeutic intervention are urgently needed. Patient‐derived xenografts (PDX) of primary ALL in immune‐deficient mice have become a powerful tool for studying leukemia biology and therapy response. In PDX mice, the immunophenotype of the patient's leukemia is commonly believed to be stably propagated. In patients, however, the surface marker expression profile of the leukemic population often displays poorly understood immunophenotypic shifts during chemotherapy and ALL progression. We therefore developed a translational flow cytometry platform to study whether the patient‐specific immunophenotype is faithfully recapitulated in PDX mice. To enable valid assessment of immunophenotypic stability and subpopulation complexity of the patient's leukemia after xenotransplantation, we comprehensively immunophenotyped diagnostic B‐ALL from children and their matched PDX using identical, clinically standardized flow protocols and instrument settings. This cross‐standardized approach ensured longitudinal stability and cross‐platform comparability of marker expression intensity at high phenotyping depth. This analysis revealed readily detectable changes to the patient leukemia‐associated immunophenotype (LAIP) after xenotransplantation. To further investigate the mechanism underlying these complex immunophenotypic shifts, we applied an integrated analytical approach that combined clinical phenotyping depth and high analytical sensitivity with unbiased high‐dimensional algorithm‐based analysis. This high‐resolution analysis revealed that xenotransplantation achieves patient‐specific propagation of phenotypically stable B‐ALL subpopulations and that the immunophenotypic shifts observed at the level of bulk leukemia were consistent with changes in underlying subpopulation abundance. By incorporating the immunophenotypic complexity of leukemic populations, this novel cross‐standardized analytical platform could greatly expand the utility of PDX for investigating ALL progression biology and assessing therapies directed at eliminating relapse‐driving leukemic subpopulations. Abstract : ALL‐PDX models show significant potential as screening platforms for clinical trials and personalized precision medicine approaches, but their utility critically depends on their ability to recapitulate clinical disease. To study phenotypic stability after xenotransplantation, we developed a translational flow cytometry platform, which revealed complex immunophenotypic shifts of the diagnostic leukemia in xenografts when analyzed at high phenotyping depth and in cross‐standardized settings. Integrating unbiased high‐dimensional analysis revealed that xenotransplantation achieves patient‐specific propagation of phenotypically stable B‐ALL subpopulations and that the observed immunophenotypic shifts result from changes in subpopulation abundance levels.